Atoms in the p-localization of stable homotopy category - Drozd, Yu.A.; Kolesnyk, P.O. (Український математичний журнал, 2014)
We study p-localizations, where p is an odd prime, of the full subcategories Sⁿ of stable homotopy category formed by CW-complexes with cells in n successive dimensions. Using the technique of triangulated categories and matrix problems, we classify the atoms (indecomposable objects) in Spⁿ for n ≤ 4(p − 1) and show that, for n > 4(p − 1), this classification is wild in a sense of the representation theory. Вивчаються p-локалiзацiї (де p — непарне просте число) повних підкатегорій Sⁿ стабільної гомотопічної категорії, що складається з CW-комплексів із клітинами в n послідовних розмірностях. Застосовуючи техніку триангульованих категорій та матричні задачі, ми наводимо класифікацію атомів (нерозкладних об'єктів) у Spⁿ Для n≤4(p−1) i показуємо, що для n>4(p—1) ця класифікація є дикою у сенсі теорії зображень.